Farmer Regeneration Through Family Farming Succession In Indonesia: Driving Factors, Challenges, And Strategies - Timban, Aimar Ridel Saviola; Mawuntu, Ignacia Mariana; Paendong, Angelica; Pua, Ester Maria Grace; Fauzi, Muh Tri Alqadri Ramadhan (AGRI-SOSIOEKONOMI, 2024)
This study aims to analyze and provide a descriptive overview of the farmer regeneration process through family farming succession. This study employed a systematic literature review following the PRISMA guidelines. The literature used in this study comprised scientific articles published in journals between 2015 and 2024. These articles were retrieved from Google Scholar and ProQuest databases using the keywords “farmer regeneration,” “farm succession,” “family farming,” and “farmer households” in both English and Indonesian. A total of 1284 publications were identified through keyword searches and 13 articles were included in the review. The results of the literature review shows that farm succession within farming families is influenced by various driving factors and challenges. To address these challenges, effective succession strategies include family socialization, mentoring programs, vocational education, youth entrepreneurship programs, and extension and training activities. Increasing the role of farmer groups in sharing information and experiences is also essential to support the sustainability of farming. Given the urgency and limited research on farm succession within farming families, further research is needed, especially studies that specifically identify strategies to enhance farm succession within farming families. Additionally, comparative studies between farm succession in different regions or countries could be conducted to understand the differences in driving factors and challenges. This could include comparisons between areas with high and low urbanization levels, as well as between different regions in Indonesia with varying cultural, social, and economic backgrounds.